Motivational dynamics in language learning, Zoltán Dörnyei, Peter D. MacIntyre and Alastair Henry Publisher: Multilingual Matters, 2015 ISBN: 978-1-78309-255-0 Pages: 430 - Pawlak, Mirosław (Studies in Second Language Learning and Teaching, 2015)
Book review